Idées simples sur certains aspects courants de l’assurance-vie - Dalpé, Jean (Assurances)

(untitled) (HEC Montréal, 1981)
Under this title, the author presents simple thoughts on some aspects of the life insurance policy: dividends and their use, the cancellation of the participating or non-participating policy, after a certain age and under certain circumstances, the increased policy loans in a period of inflation in United States and in Canada. His views are expressed in a very simple way, neglecting voluntarily the mathematical aspect of the problems. He suggests practical solutions, but admits at the start that other views might be held on the subject, depending on individual or personal circumstances or needs.